Ancient Epistemologies - Dietrich, Jan; Wagner, Thomas; Schellenberg-Lagler, Annette (Mohr Siebeck, 2024)
Antike Epistemologien.
PublicationDate: 20241028
Keywords: Hebrew Bible -- Ancient Near East -- Ancient Philosophy -- Epistemology -- Unterrichtsplanung -- Ancient Egypt -- Political theology -- Altes Testament -- Religionsphilosophie -- Antike -- Antike Religionsgeschichte -- Array